2003
DOI: 10.1094/cchem.2003.80.3.333
|View full text |Cite
|
Sign up to set email alerts
|

Stress Relaxation Behavior of Wheat Dough, Gluten, and Gluten Protein Fractions

Abstract: Cereal Chem. 80(3):333-338Relaxation behavior was measured for dough, gluten and gluten protein fractions obtained from the U.K. biscuitmaking flour, Riband, and the U.K. breadmaking flour, Hereward. The relaxation spectrum, in which relaxation times (t) are related to polymer molecular size, for dough showed a broad molecular size distribution, with two relaxation processes: a major peak at short times and a second peak at times longer than 10 sec, which is thought to correspond to network structure, and whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
59
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 31 publications
6
59
0
Order By: Relevance
“…G0 showed a strong correlation with protein (r=0.984), which could be reflected in the greater strength of gluten, thereby a high resistance upon deformation. A second correlation of G0 was with wet gluten (r=0.987), which probably is due to the fact that a greater amount of gluten causes greater resistance to deformation, and this is in agreement the study carried out by (Li et al, (2003). Finally, the last correlation of G0 was with falling number (r=0.986).…”
Section: Correlations Between Viscoelastic Characteristics and Other supporting
confidence: 86%
See 3 more Smart Citations
“…G0 showed a strong correlation with protein (r=0.984), which could be reflected in the greater strength of gluten, thereby a high resistance upon deformation. A second correlation of G0 was with wet gluten (r=0.987), which probably is due to the fact that a greater amount of gluten causes greater resistance to deformation, and this is in agreement the study carried out by (Li et al, (2003). Finally, the last correlation of G0 was with falling number (r=0.986).…”
Section: Correlations Between Viscoelastic Characteristics and Other supporting
confidence: 86%
“…In general, variation of values of τ (range 0.33 s to 0.41 s) was probably attributed at the content and type of protein, and moisture content of the wheat cultivar. This has been observed in several investigations, where it has been found that moisture and gluten properties (such as gluten strength) affect the parameters of this test (Fu et al, 1997;Larsson & Eliasson, 1996a;Li et al, 2003;Yadav et al, 2005).…”
Section: Fundamental Testsupporting
confidence: 66%
See 2 more Smart Citations
“…And other ingredients such as fat, sugar, starch and water are contained in the skeleton, which makes the gluten with elasticity and plasticity (Yu et al, 2010). Gluten proteins confer dough rheological properties such as water retention, dough adhesion and viscoelastic properties (Li et al, 2003). The mechanism of the increase in hardness during dough formation is not well understood but is generally believed to be the result of optimization of the protein interaction in the dough.…”
Section: Introductionmentioning
confidence: 99%